The Practice of Profit-Sharing Agricultural Land According to Islamic Law in Bulukumba - Mustafaenal Mustafaenal; Sodikin Sodikin (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study examines the practice of agricultural land profit-sharing in Bulukumba Regency through the lenses of Islamic law and Indonesian positive law. The traditional profit-sharing system, known as tudang sipulung, is still conducted orally without formal written agreements, often leading to inequalities in the distribution of profits. Using a descriptive-normative approach, this research analyzes how local profit-sharing practices align with Islamic legal principles, particularly concerning the muzara'ah and musaqah contracts. The findings reveal that agricultural profit-sharing in Bulukumba Regency is deeply rooted in local traditions, even as it incorporates some elements of Islamic law. However, it fails to fully embody the principles of justice outlined in both Islamic and positive law. The lack of written agreements and the observed inequalities in profit-sharing indicate a weak adherence to the principles of justice and legal certainty. Therefore, there is a significant need to integrate Islamic values into agrarian policies to strengthen distributive justice and enhance the welfare of farmers in the region.